Nation and reproduction: immigrants and their children in population discourse in Italy. Issue 1 (January 2015) - Decimo, Francesca
Abstract Italian society is undergoing significant demographic changes: on one hand, the widespread decrease in birth rates and extended life expectancies lead to a substantial aging of the population; on the other hand, rising immigration rates constitute an important factor behind the renewal and growth of young population segments. According to conventional disciplinary divisions, such changes are the established domain of demography; however, it mainly draws on ethno‐national categories to investigate them. In reference to the Italian context, this article specifically highlights the way national demography employs forecasts and value judgments derived from a qualitative and selective definition of population to address the marked increase in children born to foreign parents. By examining the reproductive behaviours of migrants in Italy, the article thus offers a wide‐ranging reflection on the social boundaries that shape the formation of an 'other' generation.